Role of Regional Financial & Assets Management Agency (BPKAD) in the Mediation Process of BPHTB & PPH - Siti Putri Indah Meilani (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The research